2019
DOI: 10.9734/mrji/2019/v28i530142
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Screening of Fungal Isolates of Palm Oil from South Eastern Nigeria for Aflatoxin and Ochratoxin Biosynthetic Genes Using Multiplex Polymerase Chain Reaction (mPCR)

Abstract: In Nigeria and many other developing countries of the world, the incidence of mycotoxin- contamination of foods and food products has attracted attention and stirred a lot of concern for food safety. This work aims at detection of aflatoxigenic and ochratoxigenic synthetic genes from fungal isolates of palm oil as a veritable means for the evaluation of foods for possible mycotoxin contamination.  In this study, fungal isolates from palm oil samples collected from the five states of South-east geopolitical zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Following the multiplex PCR assay with the primer pairs: nor-1, ver-1, omt-A, and aflR1 sequences, the results indicated that the DNA from Aspergillus flavus (4) and Aspergillus parasiticus(1) [AF4 and AP1] possessed all the four aflatoxin biosynthesis genes. A number of researchers have made similar reports on different agricultural and food products (Nwachukwu et al, 2019;Sadhasivam et al, 2017;Gherbawy et al, 2016;Degola et al, 2007). The DNA of AF2 and AF3 indicated positive reaction for the following genes: nor-1 gene, ver-1 gene and aflR gene.…”
Section: Discussionmentioning
confidence: 88%
“…Following the multiplex PCR assay with the primer pairs: nor-1, ver-1, omt-A, and aflR1 sequences, the results indicated that the DNA from Aspergillus flavus (4) and Aspergillus parasiticus(1) [AF4 and AP1] possessed all the four aflatoxin biosynthesis genes. A number of researchers have made similar reports on different agricultural and food products (Nwachukwu et al, 2019;Sadhasivam et al, 2017;Gherbawy et al, 2016;Degola et al, 2007). The DNA of AF2 and AF3 indicated positive reaction for the following genes: nor-1 gene, ver-1 gene and aflR gene.…”
Section: Discussionmentioning
confidence: 88%